Protection Policy for Breastfeeding Mothers: An Insight from Midwife Ethical Code and Breastfeeding Rights - Arief Budiono; Dewi Iriani; Aminuddin Mustaffa; Siti Soekiswati; Abdullah Al Mamun (Jurnal Hukum, 2026)
Midwives are legally required to support postpartum women in exercising their right to breastfeed. In practice, many midwives provide formula milk, ignoring the mother's right to breastfeed and potentially harming both mother and baby. The purpose of this paper is to investigate the legal and ethical considerations surrounding midwives and mothers in relation to breastfeeding rights, emphasizing the need for transparency between midwives and mothers. This research uses empirical methods and a qualitative approach. The findings in this paper indicate that mothers are willing to provide informed consent, including information about any conditions that prevent breastfeeding immediately after delivery. Health Law Number 17 of 2023 mandates exclusive breastfeeding and imposes strict sanctions for those who prohibit breastfeeding without medical reasons. Despite this regulation, some midwives still provide formula milk with the verbal consent of postpartum mothers for medical reasons without adequate medical examination.